Stormbreaker - Horowitz, Anthony (London Walker Books, 2005)
After the death of the uncle who had been his guardian, fourteen-year-old Alex Rider is coerced to continue his uncle's dangerous work for Britain's intelligence agency, MI6.
Keywords: Orphans -- Terrorism -- England